Lucain et la mémoire de Pharsale : le chant VII de la Pharsale comme tombeau poétique de Rome - Pierre-Alain Caltot (Pallas, 2019)
If the motive of Rome’s death is already evoked in the Augustan era, it finds an original reinterpretation in Lucan’s epic. Indeed, Lucan does celebrate a real disaster: Pharsalus consecrates the death of Rome and Lucan’s epic, especially book VII, appears like a poetic tomb of the Res publica romana. Lucan presents Pharsalus as a total disaster whose scope is at once human, historical and political, but also mythical and cosmic. The poet finally presents this battle as a poetic disaster, where the dactylic hexameter is reconfigured stylistically, not to celebrate the exploits of the past, but as a memorial for a paroxysmal catastrophe – the death of Rome.